Tuning Analysis and Optimization of a Cluster-Based Aiming Methodology for Solar Central Receivers - García, Jesús; Barraza, Rodrigo; Soo Too, Yen Chean; Vásquez Padilla, Ricardo; Acosta, David; Estay, Danilo; Valdivia, Patricio (Frontiers in Energy Research, 2022)
The challenges encountered while concentrating solar radiation from multiple heliostats into a relatively small receiver have inspired numerous aiming methodologies to distribute such concentrated radiation. Likewise, this concentrated radiation, denominated heat flux, needs to satisfy certain constraints that primarily depend on the receiver geometry, its building materials, the operating mass flow of the heat transfer fluid, and the overall solar radiation conditions. A recent study has demonstrated the effectiveness of an aiming strategy wherein a group of heliostats use a single parameter for the entire cluster and achieve the desired heat flux profile by adjusting the tuning parameters. Along similar lines, the current study was conducted to find the optimal values and the effect of two such parameters. The first parameter limits how far the aiming point of the heliostat can move from the equator line of the receiver, while the second represents its direction (upward or downward) from this line toward the edge of the receiver. Each section of a solar field was subdivided; both parameters were estimated for each subgroup, and their effect on the heat flux profile was determined. Furthermore, a parametric study was conducted using three sets of constraints for the optimization procedure. This procedure resulted in a heat flux profile that accomplished the constraints given by the allowable flux density for the receiver during the design day. The improvement using the optimal tuning parameters for the design scenario reached around 27%. Further analysis of the set of optimal values showed an adequate performance of the system at different times of the day and different days of the year. Finally, this study demonstrates how the calculated values function as a starting point for implementing the aiming methodology in different solar field and receiver combinations.